ACTIVITIES CURRICULUM DEVELOPMENT TO ENHANCE CREATIVE INNOVATION ABILITIES INTEGRATED LOCAL WISDOM OF SECONDARY STUDENTS’ NONGBUALUMPHU PROVINCE: การพัฒนาหลักสูตรกิจกรรมการคิดสร้างสรรค์เพื่อส่งเสริมความสามารถในการสร้างนวัตกรรมที่บูรณาการภูมิปัญญาท้องถิ่นของนักเรียนมัธยมศึกษา จังหวัดหนองบัวลำภู - Sopakool, Amnart; Tanunchaibutra, Prin; Termtachatipongsa, Phairoth (Journal of Education and Innovation, 2023)
The objectives of this research were to 1) study the basics of the creative activities curriculum, 2) create a creative activities curriculum, and 3) study the results of the creative activities curriculum to promote the abilities to create innovation integrated local wisdom. There are 3 phases, the study of basic data, creation of activities curriculum and curriculum implementation. The target group was students at the secondary school level in Nong Bua Lam Phu province. The results were; 1. creative activities curriculum that integrated local wisdom in educational institutions or policies that led to practice were not clear. The school operated in accordance with an urgent policy. Especially during the period of being followed up by a qualified follow-up assessment or supervision from external educational agencies, some of them had not achieved continuous and sustainable practice. 2. The curriculum had been developed, was 7 elements: principles and rationale, philosophy, concepts and theories, objectives, structure, activity guidelines, media and learning resources, measurement, and evaluation. The contents consisted of 1) Inspire, 2) Search for information, 3) Study of wisdom sources, 4) create innovation, and 5) disseminate innovation to the community. 3. The creative level of the students had a high overall grade point average after implementing was 48.9. The students had an excellent evaluation of the innovation ability of the students 89.1, the results of the assessment of the innovation process, the mean of 4.3 was in an incredibly good level.